Pengaruh Self Efficacy, Etos Kerja dan Pengembangan Karir Terhadap Komitmen Organisasional Pegawai Pada Badan Pendapatan Daerah Kabupaten Lombok Timur - Ningsih, Surya; Suryatni, Mukmin (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of self efficacy (X1), work ethic (X2) and career development (X3) on organizational commitment (Y) of employees at the East Lombok Regency Regional Revenue Agency. The type of research used is causal associative research. Tests were conducted on 76 employees of the Regional Revenue Agency of East Lombok Regency. The data collection method uses the census method. In conducting data analysis, multiple linear regression analysis was used with the SPSS version 30 program application tool: (1) Self efficacy has a positive and significant effect on organizational commitment, (2) Work ethic has a positive and significant effect on organizational commitment, (3) Career development has a positive and significant effect on organizational commitment. So it is concluded that the higher the self efficacy, the higher the organizational commitment, on the contrary, if the self efficacy is low, the lower the organizational commitment. The higher the work ethic, the higher the organizational commitment, otherwise if the work ethic is low, the lower the organizational commitment. The more appropriate career development, the higher organizational commitment will be, on the contrary, if career development is not appropriate, organizational commitment will be lower.